Determinants of knowledge sharing behaviour among academics in United Arab Emirates - Skaik, Huda Alami; Othman, Roslina (IGI Global, 2014)
The main objectives of this research are to (i) investigate the practice of knowledge sharing among academics, and (ii) examine the relationship between knowledge sharing behaviour and its predictors based on the Theory of Planned Behaviour. Data were collected through an online survey using a questionnaire from academics in public universities. Using SPSS and PLS-SEM, data analysis process involved (i) analysis of descriptive statistics to evaluate knowledge sharing practice, (ii) assessment of the measurement model to evaluate items reliability and validity, and (iii) assessment of the structural model to evaluate its validity, path coefficients, and test the hypotheses. The results showed a great extent of knowledge sharing practice. They proved that academics’ knowledge sharing behaviour is significantly influenced by intention, which is influenced by attitude, subjective norms, and self-efficacy. Contrary to the theory, the results showed that controllability does not influence intention.